Ser cuidador de paciente com acidente vascular cerebral: histórias não contadas - Moura, Kalina Siqueira de (2014)
The present study aimed to understand the experience of being a family caregiver of a patient with Cerebrovascular Accident (CVA). The relevance of the study is to prove existence of a large number of caregivers of incapacitated patients, due to the CVA and it is not an academic research object, according to the literature. It is a qualitative research, which the guiding principle is the oral history of life, according to the theoretical foundation and operating of Meihy. Therefore, the following steps were highlighted: the target community, composed of all family caregivers of CVA patients; the colony, composed by family caregivers of CVA patients assisted by Home Care Service (HCS) of the Hospital José Pedro Bezerra (HJPB), in the city of Natal/RN; the network was composed of six caregivers who met the criteria for inclusion, and as zero point the first volunteer group. The population was composed of all family caregivers of patients attended by the HCS, of the HJPB having been addressed through interviews. For the empirical research there was the consent of that institution and approval by the Ethics Committee in Research of the Federal University of Rio Grande do Norte as CAAE 24569413.0.0000.5537 and, above all, with the acquiescence of employees in participating in the investigation, signing an informed consent. Of the empirical material, five categories of analysis were identified: the sense of being a caregiver; what has changed in the life of the caregiver; the feelings emerge in the relationship of care; the distance from family and friends; difficulties faced by the caregiver. The results show that the caregiver's life goes through profound transformations within the family as well as in all spheres of life. For the caregivers, assuming the care of a relative with CVA means renunciation and donation, compromising sometimes the individual projects and the family as a whole. In addition, they point out the confrontation of difficulties within the the assistance and humanization in healthcare, information, physical and emotional overload, as well as financial problems. Despite all the adversities that compromise the caregiver's life, it was possible to identify attitudes of resilience among caregivers, making them their daily life less strenuous and with more lightness. It is expected, therefore, that this research can contribute to a better orientation of professionals with the caregivers